2014
DOI: 10.3126/jkmc.v2i3.9934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in individuals undergoing comprehensive cardiac and general medical check-up at Kathmandu Medical College Teaching Hospital

Abstract: Background: Metabolic syndrome represents a constellation of metabolic derangements including insulin resistance, diabetes mellitus, obesity, dyslipidaemia and cardiovascular disease. Since it is associated with higher risk of coronary artery disease and diabetes mellitus, timely detection is important. Objectives: The main objective of the study was to find out the prevalence of metabolic syndrome in individuals undergoing comprehensive cardiac and general medical check-up at Kathmandu Medical College Teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
1
2
Order By: Relevance
“…16 Similarly, in study done by Karki et al prevalence was found to be 14.4% among individuals undergoing comprehensive cardiac and general medical checkup in Kathmandu. 19 The prevalence was found to be quite high comprising 20 Prevalence of MS was found to be slightly higher among male in this study with male:female = 1.09:1; however it was found to more prevalent among female in studies done by Timalsina et al, Karki et al, and Srinivasan et al comprising 62.5%, 75.7%, and 65.2% respectively. [18][19][20] Metabolic syndrome is most commonly associated with advancing age and obesity.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…16 Similarly, in study done by Karki et al prevalence was found to be 14.4% among individuals undergoing comprehensive cardiac and general medical checkup in Kathmandu. 19 The prevalence was found to be quite high comprising 20 Prevalence of MS was found to be slightly higher among male in this study with male:female = 1.09:1; however it was found to more prevalent among female in studies done by Timalsina et al, Karki et al, and Srinivasan et al comprising 62.5%, 75.7%, and 65.2% respectively. [18][19][20] Metabolic syndrome is most commonly associated with advancing age and obesity.…”
Section: Discussioncontrasting
confidence: 44%
“…19 The prevalence was found to be quite high comprising 20 Prevalence of MS was found to be slightly higher among male in this study with male:female = 1.09:1; however it was found to more prevalent among female in studies done by Timalsina et al, Karki et al, and Srinivasan et al comprising 62.5%, 75.7%, and 65.2% respectively. [18][19][20] Metabolic syndrome is most commonly associated with advancing age and obesity. The findings of this study are in concordance with the finding of other studies.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation